Pengaruh E-service quality, kualitas informasi dan perceived value terhadap loyalitas pelanggan melalui kepuasan pelanggan grabbike - Punang Biru Vicramaditya (Journal of Business & Banking, 2020)
This study aims to determine the effect of electronic service quality, information quality,and perceived value on customer loyalty through online motorcycle taxi customersatisfaction. This study used GrabBike as the subject and the dfata were analyzed usinga quantitative analysis by using SmartPLS 3. The data were obtained by purposivesampling technique and the researchers distributed the questionnaires via google form to154 GrabBike customers as the respondents. The results indicated that e-service qualityand perceived value have a positive and signifcant effect directly on customer satisfactionand customer loyalty, while information quality has a positive and signifcant effecton customer satisfaction but negative and they insignifcant affect customer loyalty.The results of the indirect effect test show that e-service quality, information qualityand perceived value have a positive and signifcant effect on customer loyalty throughcustomer satisfaction. Implications of this study was that online motorcycle taxi shouldimprove its information quality so that customers are safe and comfortable that will leadto satisfaction and loyalty.